Shattered sanctuary [large type] - Mehl, Nancy (Mehl, Nancy. Erin Delaney mysteries, 2025)
"Grappling with the aftermath of a tragic incident that altered her life, ex-police officer and bestselling mystery author Erin Delaney finds solace in the tranquility of a cabin nestled deep in the Smoky Mountains. But her newfound peace is shattered when cries pierce the night, hinting at a haunting presence lurking in the woods. When local police chief Adrian Nightengale seeks her help with a baffling murder case, she is thrust back into the world of crime solving. As they delve into the investigation, Erin's intuition reveals chilling truths about the killer's motives and methods. Joined by the enigmatic Kaely Quinn-Hunter, a former FBI behavioral analyst, Erin not only embarks on a quest to stop a merciless serial killer but also confronts the ghosts of her past. In a race against time, Erin must defeat her own demons while outmaneuvering a cunning killer or risk becoming the next victim in a deadly game of cat and mouse."--